The Dutch and English East India Companies : Diplomacy, Trade and Violence in Early Modern Asia - Mostert, Tristan; Clulow, Adam; Clulow, Adam (Amsterdam Amsterdam University Press)
A ground-breaking collection of essays that explores the place of the Dutch and English East India Companies in Asia and the nature of their interactions with Asian rulers, officials, merchants, soldiers and brokers. The Dutch and English East India Companies were formidable organizations that were gifted with expansive powers that allowed them to conduct diplomacy, raise armies and seize territorial possessions. But they did not move into an empty arena in which they were free to deploy these powers without resistance. Early modern Asia stood at the center of the global economy and was home to powerful states and sprawling commercial networks. With contributions from the most innovative historians working on the companies today, this book presents new ways to understand these organizations by focusing on their diplomatic, commercial and military interactions with Asia.
English
Keywords: Economic history; History; East India Companies; Empire; Trade; Diplomacy; Warfare